2002
DOI: 10.1086/343048
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Conditions, Treatment, and Health Maintenance in Older Persons with Human Immunodeficiency Virus Infection in New York City

Abstract: We retrospectively examined comorbid conditions and health maintenance in 198 patients aged > or =55 years who attended 3 New York City human immunodeficiency virus (HIV) clinics between 1 January 1990 and 30 June 1998. Annual influenza and pneumococcal vaccinations within 5 years were given in 82% and 86% of patients, respectively. Among 57 women, 79% had a Papanicolaou smear within 1 year, and 53% had a mammogram within 2 years. Of 165 patients who received care after 1 July 1996, 147 (89%) had comorbid cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 22 publications
2
41
1
4
Order By: Relevance
“…Gutiérrez et al 50 observed that the greater progression to AIDS events or death among older people persists after adjusting for CD4 lymphocyte count in patients on HAART and a sustained virological response. The increased mortality in older patients may be related to age as a predictor of disease progression, diagnostic delay, 30,32,[34][35][36][37][38] the presence of comorbidities, 17,18,29,30,51 or the presence of AIDS or not AIDS, 17,52,53 among others. Other authors have not found an association between mortality and age.…”
Section: Discussionmentioning
confidence: 99%
“…Gutiérrez et al 50 observed that the greater progression to AIDS events or death among older people persists after adjusting for CD4 lymphocyte count in patients on HAART and a sustained virological response. The increased mortality in older patients may be related to age as a predictor of disease progression, diagnostic delay, 30,32,[34][35][36][37][38] the presence of comorbidities, 17,18,29,30,51 or the presence of AIDS or not AIDS, 17,52,53 among others. Other authors have not found an association between mortality and age.…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide data on different populations at different time points: New York City clinic patients age 55 or older between 1996-1998, 13 U.S. veterans receiving care from 1999 to 2000, 14 and U.S. veterans receiving care from 1997 to 2004. 15 In a sample of 165 HIV-positive clinic patients aged 55 or older, 13 89% had at least one comorbid condition. The most frequently occurring were hypertension (41%), chronic airway disease (29%), diabetes mellitus (22%), arthritis (18%), hepatitis C virus infection (16%), and coronary artery disease (14%).…”
mentioning
confidence: 99%
“…In addition, a study showed that these individuals have less access to healthcare services, which can contribute to this disparity (16) .Regarding sex, there is no consensus about what would be a risk factor, although males are more prevalent in studies as a risk factor for SAH (10,21,25) . Advanced age, especially over 50, becomes a key factor for the development of SAH in this population.Other studies show that SAH is the most important comorbidity among the elderly (28)(29) . Therefore, elders with HIV/AIDS are more vulnerable, so we noticed they have more chronic conditions than elders who do not live with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 94%